Comprehensive security estimation of departmental networks - T. A. Andryianava; S. B. Salomatin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The methods of comprehensive security estimation of departmental networks are examined. Objects and methods of monitoring of the departmental networks defined by taking into account the conditions and the specific activity of the state bodies. The method for evaluation of information security of departmental networks based on the theoretical graph models and expert security risks assessment are proposed in this article.